Mixed convection boundary-layer flow along a vertical surface embedded in a porous medium with a convective boundary condition. - Y.Y., Lok (2013)

(untitled)
An analysis of the mixed convection boundary-layer flow on one face of a semi-infinite vertical surface embedded in a fluid-saturated porous medium is presented. It is assumed that the other face of the surface is in contact with a hot or cooled fluid maintaining the surface at a constant "temperature Tf .